PENGARUH MODEL PEMBELAJARAN TEACHING FACTORY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GAMBAR TEKNIK KELAS X DPIB DI SMK NEGERI 1 PERCUT SEI TUAN - Yosep P. Sinaga; Rumilla Harahap (STKIP Subang, 2026)
This study aims to find out the difference in learning outcomes of engineering drawing elements using the Teaching Factory learning model and the Discovery Learning learning model in grade X DPIB students at SMK Negeri 1 Percut Sei Tuan. This research was carried out at SMK Negeri 1 Percut Sei Tuan in the even semester of the 2025/2026 Academic Year. The research sample consisted of 2 classes, namely class X DPIB 1 with a total of 31 students for the Teaching Factory learning model and class X DPIB 2 with a total of 31 students for the Discovery Learning learning model. The research method used is quantitative with the Quasi Eksperiment Design research type which compares the learning outcomes of students taught using the Teaching Factory learning model and the Discovery Learning learning model. The data analysis technique used the t-test with a significant level of α = 0.05. The results of this study show that there is a significant difference in learning outcomes in students taught with the Teaching Factory learning model compared to students taught with the Discovery Learning learning model. The average learning outcome taught with the Teaching Factory model is 83.5 while students taught with the Discovery Learning learning model are 72.3.